Borders in the South: Migration News in South Asia and the Pacific - Zaman MA; Das J (FU Berlin, University of Erfurt, 2016)
In the age of unprecedented movement of people, many migrants end up in the industrialized countries but originate from all over the world. A fuller picture of migration journalism thus warrants examining news from both the ‘source’ and ‘receiving’ countries of migration. However, most of the studies undertaken in this particular area deal with the issues from the perspectives of North America and Europe (i.e., ‘receiving’ countries), an approach which is inconsistent with the broad goal of comparative studies. The current study examines migration news from both the source and receiving countries. Given that South Asia and the Pacific are two regions that tend to be overlooked in the comparative studies literature, we studied the coverage of migration issues in six prominent English-language newspapers from six countries of these regions (Australia, Bangladesh, India, New Zealand, Pakistan and Sri Lanka) over a four-month period in 2014. Our study utilized an exploratory frame analysis to determine whether, in line with several earlier studies, issues of migration are depicted as a crisis to be managed in the receiving countries. Moreover, we examined the emphasis attached to the subject matter by the source countries’ media. The findings suggest that the media frames in receiving countries are more diverse than expected. While newspapers in some countries follow the previously found crisis frame, others highlight the economic benefits of migration. Similarly, in the source countries, the frames are varied. Most newspapers portray migration as a problem to be solved, but some do focus on protecting the interests of the migrants.
Keywords: migration news; news frame; comparative journalism, South Asia; Pacific, crisis, welfare